Analisis Kinerja Perawat Pelaksana Terhadap Pelayanan Di Ruangan Penyakit Dalam Rumah Sakit Kayuagung Tahun 2017 - Aleksander, Denis (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Hospital is health care institutions that provide full-scale personal health services that provide inpatient, outpatient and emergency care services. One of the programs that must be run is performance management which is a technique to assess HR performance. Performance or performance of an employee is distinguished in quality and quantity and generated according to the responsibilities given to him. The research design uses quantitative research method with analytical survey method with Cross Sectional approach. Population in this research as many as 45 people with technique of total sampling. Data analysis was done by univariate analysis, bivariate using Chi-Square test (? = 0,05) and multivariate with logistic regression. The result of univariate analysis was obtained for age 95,6%, gender 91,1%, education level 75,6%, work time 55,6%, training 55,6%, leadership 55,6%, and career development 53,3 %. For executive nurse performance 51.1% stated good. The result of bivariate analysis that age factor (p = 1,000), education level (p = 0,165), training (p = 0,017), leadership (p = 0,017), and career development (p = 0,003). Multivariate analysis results obtained training that affect the performance of nurses. Based on the research result, it can be concluded that there are 2 (two) factors that are not related to the performance of the nurses and there are 3 (three) factors related to the performance of the nurses. It is suggested that the performance of nurses in the Hospital of Internal Medicine of Kayuagung Hospital will be maintained and improved